Evaluating Business Curriculum in Applied Universities: A CIPP-Based Framework - Wenbin, Hao (International Conference on Fundamental and Applied Research (I-CFAR), 2026)
In response to China’s initiative to advance “New Humanities” and “New Business,” this study highlights the urgent need for a systematic framework to evaluate innovative curricula such as the interdisciplinary “Big Business” course in applied undergraduate institutions. The primary aim is to construct a comprehensive evaluation system based on the CIPP (Context, Input, Process, Product) model to diagnose implementation challenges and provide actionable guidance for improvement. Adopting a qualitative design research approach, the framework was developed through a systematic literature review, indicator extraction and synthesis, and logical validation. The finalized system encompasses four primary and ten secondary indicators aligned with the CIPP dimensions. Its application reveals several systemic challenges, including misalignment between curriculum objectives and content, insufficient investment in teaching resources, imbalances between student engagement and cognitive load, and limited alignment with industry needs. The study concludes that holistic, system-level reforms are essential for ensuring the curriculum’s effectiveness. The key contribution lies in offering a validated and practical tool for educators to improve curriculum quality, as well as a theoretical foundation for evaluating complex interdisciplinary programs.